2019
DOI: 10.1177/0003489419848786
|View full text |Cite
|
Sign up to set email alerts
|

Survival Outcomes for Advanced Cutaneous Squamous Cell Carcinoma of the Head and Neck

Abstract: Objectives: Survival outcomes for advanced non-melanoma skin cancers of the head and neck treated with surgical resection are not well described in the literature. We aimed to describe outcomes for T3 and T4 cutaneoous squamous cell carcinoma of the head or neck treated with surgical resection at 1 tertiary academic medical center. Methods: We analyzed a retrospective cohort of patients diagnosed with T3 or T4 cutaneous squamous cell carcinoma (SCC) of the head or neck from 2005 to 2016 treated with definitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
4
9
0
Order By: Relevance
“…In 75% of patients, the main surgery was total primary resection with reconstruction followed by exenteration and temporalectomies, showing an aggressive presentation, similar to other developing countries 35 . Our data did not find an association between the type of primary surgery and survival, unusual since such a correlation is expected, however, there is comparable studies 34,38,39 .…”
Section: Synopsis Of New Findingssupporting
confidence: 47%
See 1 more Smart Citation
“…In 75% of patients, the main surgery was total primary resection with reconstruction followed by exenteration and temporalectomies, showing an aggressive presentation, similar to other developing countries 35 . Our data did not find an association between the type of primary surgery and survival, unusual since such a correlation is expected, however, there is comparable studies 34,38,39 .…”
Section: Synopsis Of New Findingssupporting
confidence: 47%
“…In univariate and multivariate analysis, primary tumor site, histopathological characteristics and margins did not affect the OS, attributed to retrospective data bias [33][34][35] . Interestingly, our study found 90.5% of patients with comorbidities (20% immunosuppressed due transplant organ), having main role on developing progressively metastases from primary to parotid/neck [36][37][38] .…”
Section: Synopsis Of New Findingsmentioning
confidence: 64%
“…7,13 This probably reflects differential local referral patterns, and explains the relatively high rate of burring in our series, i.e., burring of outer table of the cranium for cases where the deep margin was narrow but where gross/microscopic bone invasion was not present.…”
mentioning
confidence: 77%
“…This was an unexpected finding as the association between immunosuppression and worse disease outcomes has been documented in several previous studies including those from our institution, but this was likely due to the low number of patients who were immunosuppressed in our cohort. 7,14,15 Molecular or genetic markers may offer greater accuracy in identifying aggressiveness of disease compared with morphological characteristics (this is beyond the scope of this article, but is an active area of research at our institution). 16 Comparison with Emerging Therapies Surgery and PORT is current standard of care for advanced cSCC, with concurrent chemoradiotherapy being routine for some institutions in cases where there is extranodal extension in regional metastasis.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation